Зажигание капель водоугольного топлива в потоке воздуха; Химия твердого топлива; № 3 - Захаревич А. В. Аркадий Владимирович; Саломатов В. В. Владимир Васильевич; Стрижак П. А. Павел Александрович; Сыродой С. В. Семен Владимирович (2017, 2017)
Заглавие с экрана